Clinical Significance of Albumin- and Bilirubin-Based Biomarkers in Glaucoma: A Retrospective Case-Control Study. (4th March 2022) - He, Chong; Zhang, Gao; Fu, Jing; Zhang, Rui; Li, An; Liu, Donghua; Li, Binghong; Chen, Yang; Deng, Bolin; Chen, Yilian; Shuai, Ping; Lu, Fang
Abstract : Glaucoma is the second leading cause of global blindness. The etiology of glaucoma is complicated. In addition to elevated intraocular pressure (IOP), several other mechanisms have been implicated in pathogenesis, such as oxidative stress and systemic inflammation. Serum albumin (ALB) and bilirubin (BIL) have been reported to have potent antioxidant properties and contribute to maintain redox homeostasis in various diseases. However, associations between these parameters and glaucoma remain mostly unknown. Here, we conducted a retrospective case-control study, revealing that serum ALB, total BIL (TBIL), and indirect BIL (IBIL) levels were markedly lower in glaucoma patients than those in healthy controls. Furthermore, the neutrophil-to-ALB (NAR), neutrophil-to-TBIL (NTBR), and neutrophil-to-IBIL (NIBR) ratios were greatly higher in glaucoma. Additionally, interestingly, lower ALB and BIL levels and higher NAR, NTBR, and NIBR were associated with severer glaucomatous visual impairment, and NAR, NTBR, and NIBR showed good accuracy as diagnostic tests for glaucoma severity, suggesting these indices might be useful as discriminative biomarkers for disease severity. Our current findings demonstrate associations between ALB, BIL, NAR, NTBR, NIBL, and glaucoma. It might be useful to use NAR, NTBR, and NIBR as predictive markers for disease severity and employ ALB/BIL as alternative therapy or adjuvant medicines in glaucoma patients.